INCREASING STUDENT’S PROFESIONAL COMPETENCY AS PROSPECTIVE TEACHERS IN TEACHER PROFESIONAL COURSE - Nurmiah Muin (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to see the increase in the professional competence of prospective teacher students including: the ability to open learning, mastery of the material, clarity of material presentation, the ability to carry out variations in learning, ask questions, manage learning classes, and the suitability of time and learning materials. The subjects of this classroom action research were students majoring in Indonesian Language and Literature Education Class of 2020, Makassar Muslim University. The data collection technique used observation with quantitative qualitative data analysis techniques. The results show an increase in the average component of teacher professional competence which consists of the component opening lessons from 51.03 to 74.75. Mastery of the material from 50.74 to 76, 18. Clarity in the delivery of material 48.82, to 77.35. The ability to carry out variations in learning from 66.76 to 76.62. The ability to ask 48.82 to 74.26. Ability to manage class 58.82 to 75.29. Ability to close the lesson 66.76 to 76.62. Timeliness and material 67.28 to 78.76. So, the five-step active learning method can improve the learning outcomes of teaching profession courses, especially the professional competence of teachers as one of the competencies that must be possessed by teaching staff.